2007
DOI: 10.1086/511296
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistical Studies on the Irradiation of Methanol in Extraterrestrial Ices

Abstract: Pure ices of amorphous methanol, CH 3 OH(X 1 A 0 ), were irradiated at 11 K by 5 keV electrons at 100 nA for 1 hr. These energetic electrons simulate electronic energy transfer processes that occur as interstellar ices, comets, and icy solar system bodies are subjected to irradiation from MeV ions and secondary electrons produced in this process. The results were analyzed quantitatively via absorption-reflection-absorption Fourier transform infrared ( FTIR) spectroscopy, with the identification of new species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
171
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(194 citation statements)
references
References 70 publications
19
171
2
2
Order By: Relevance
“…HCO can be identified from its ν 2 band between 1840 and 1860 cm −1 (Gerakines et al 1996;Bennett et al 2007). No stable species considered in this study absorbs in this region.…”
Section: Identification Of Ch 3 Oh Ice Uv Photoproductsmentioning
confidence: 91%
See 4 more Smart Citations
“…HCO can be identified from its ν 2 band between 1840 and 1860 cm −1 (Gerakines et al 1996;Bennett et al 2007). No stable species considered in this study absorbs in this region.…”
Section: Identification Of Ch 3 Oh Ice Uv Photoproductsmentioning
confidence: 91%
“…A few studies exist on the formation of complex molecules from ion bombardment of pure CH 3 OH ice, though similarly to the UV photolysis experiments, the formation of more complex molecules than CH 3 OH is in general not quantified (Baratta et al 2002;Bennett et al 2007). Bennett et al (2007) identified HCOOCH 3 , HOCH 2 CHO and (CH 2 OH) 2 , mainly based on comparison with calculated spectra and desorption patterns following irradiation, but provided only upper limits of their formation rates.…”
Section: Article Published By Edp Sciencesmentioning
confidence: 99%
See 3 more Smart Citations